Trichuris dolichotis Morini, Boero & Rodriguez, 1955 (Nematoda: Trichuridae) in dolichotis patagonum (Zimmermann, 1780) (Rodentia: Caviidae) of center for wildlife conservation, San Juan, Argentina - González-Rivas, Cynthia J. (2023)
In Argentina, there is one record of the nematode Trichuris dolichotis Morini, Boero & Rodriguez, 1955 (Nematoda: Trichuridae) parasitizing the mara Dolichotis patagonum (Zimmermann, 1780), which corresponds to its original description in 1955. In June 2023, at the Wildlife Rehabilitation Center, San Juan province, a specimen of mara male D. patagonum died and the necropsy´s results are under investigation at the moment. The post-mortem identified (n= 5) female nematodes of T. dolichotis in the intestine. In the present study we present the second record after 58 years of not reporting its presence, being the first record for the province of San Juan and the second for Argentina. The present work contributes to the knowledge of the mammalian parasite fauna of Argentina.